General election based on the principle of Luber-Jurdil and its development in Indonesia - Silalahi, Fernando; Tampubolon, Manotar (Technium Social Sciences Journal, 2021)
This qualitative study analyses the implementation of Indonesia’s General Election (PEMILU), based on the principles of it being Direct, Public, Free, Confidential, Honest and Fair (LUBER-JURDIL), post-reformation, and its development in Indonesia from the perspective of Dahl’s Theory of Power. For General Elections in Indonesia, the principle of LUBER JURDIL has been implemented; however, BAWASLU is indecisive, enabling elements to try to undermine the electoral process. Violations occurred during the campaign because of weak law enforcement and community mobilisation in the name of religion. This is damaging the purpose of the election, which delegation of political representation. As one of the largest democracies in the world, Indonesia must be able to live up to being the best country for implementing democracy, by upholding the principle of LUBER JURDIL. This study uses the concept of democracy to assess the problems of mechanism and the implementation of the principle of LUBER JURDIL in previous and upcoming Indonesian elections. By improving the implementation of democratic elections, changes the leadership and national development, the people’s expectations for the realization of Indonesia as Indonesia a Welfare State.